К проблеме развития мелкой моторики у детей с аутизмом - Кафьян, Э. М.; Саруханян, К. А.
The article presents children with autism the delicate motor skills the importance of development, showing how a specially organized and consistent work will develop these children attention, memory, communication and interaction skills.
Keywords: Аутизм